Sákit Pighati and Pag-asa: A Pastoral Reflection on Suffering During the COVID-19 Pandemic in the Philippines - Cordero, Dalmacito A. (J Relig Health, 2021)
This article explores the concept of suffering as experienced by Filipinos during the COVID-19 pandemic. It draws inspiration from their narratives about how they faced, managed, and struggled during this tragic event. Their experiences were interpreted and analyzed concerning Filipino culture and tradition using a modified form of thematic analysis. Findings revealed three contextualized themes: sákit (pain), pighati (grief), and pag-asa (hope). These themes are then discussed in the light of John Paul II's Salvifici Doloris. A meaningful pastoral reflection on the basic realities of suffering is formulated to clarify our understanding of such a crisis.